Body dissatisfaction and weight control behaviour in children with ADHD: A population-based study - Rinehart, Nicole; Sciberras, Emma; Sciberras, E; Bisset, Matthew; Bisset, M; Rinehart, N (My University, 2019)
Although attention-deficit/hyperactivity disorder (ADHD) is associated with eating disorders (EDs), it is unclear when ED risk emerges in children with ADHD. We compared differences in body dissatisfaction and weight control behaviour in children with/without ADHD aged 12–13 years concurrently, and when aged 8–9 and 10–11 years, to determine when risk emerges. We also examined differences by ADHD medication status at each age. This study uses waves 1–5 from the Longitudinal Study of Australian Children (n = 2323–2972). ADHD (7.7%) was defined at age 12–13 years by both parent- and teacher-reported SDQ Hyperactivity–Inattention scores > 90th percentile, parent-reported ADHD diagnosis and/or ADHD medication treatment. Children reported body dissatisfaction and weight control behaviour at 8–9, 10–11 and 12–13 years. Children with ADHD had greater odds of body dissatisfaction at ages 8–9 and 12–13 years. Comorbidities drove this relationship at 8–9 but not at 12–13 years [adjusted odds ratio (AOR): 1.6; 95 % CI 1.1–2.4; p = 0.01]. At 12–13 years, children with ADHD had greater odds of both trying to lose and gain weight, regardless of BMI status. Comorbidities drove the risk of trying to lose weight in ADHD but not of trying to gain weight (AOR 2.3; 95% CI 1.1–4.6; p = 0.03), which is likely accounted for by ADHD medication treatment. ADHD moderately increases body dissatisfaction risk in children aged 8–9 and 12–13 years. Clinicians should monitor this and weight control behaviour throughout mid-late childhood, particularly in children with comorbid conditions and those taking ADHD medication, to reduce the likelihood of later ED onset.
Keywords: Health -- Body size, BMI, Body image; Children -- Adolescents and youth; Health and wellbeing; Childhood and child development